A sparse orthogonal collimator for small animal intensity‐modulated radiation therapy. Part II: hardware development and commissioning. Issue 12 (4th November 2019) - Woods, Kaley; Neph, Ryan; Nguyen, Dan; Sheng, Ke
Abstract : Purpose: A dose‐modulation device for small animal radiotherapy is required to use clinically analogous treatment techniques, which will likely increase the translatability of preclinical research results. Because the clinically used multileaf collimator (MLC) is impractical for miniaturization, we have developed a simpler, better‐suited sparse orthogonal collimator (SOC) for delivering small animal intensity‐modulated radiation therapy (IMRT) using a rectangular aperture optimization (RAO) treatment planning system. Methods: The SOC system was modeled in computer‐aided design software and fabricated with machined tungsten leaves and three‐dimensional (3D) printed leaf housing. A graphical user interface was developed for controlling and calibrating the SOC leaves, which are driven by Arduino‐controlled stepper motors. A Winston‐Lutz test was performed to assess mechanical alignment, and abutting field and grid dose patterns were created to analyze intra‐ and intercalibration leaf positioning error. Leaf transmission and penumbra were measured over the full range of gantry angles and leaf positions, respectively. Three SOC test plans were delivered, and film measurements were compared to the intended dose distributions. The differences in maximum, mean, and minimum, as well as pixelwise absolute dose differences, were compared for each structure, and a gamma analysis was performed for the target structures using criteria of 4% dose difference and 0.3 mm distance to agreement. Results: The Winston‐Lutz test revealed maximum directional offsets between the SOC and primary collimator axes of 0.53 mm at 0° and 0.68 mm over the full 360°. Upper and lower abutting field patterns had maximum dose deviations of 18.8 ± 3.1% and 15.5 ± 2.9%, respectively, and grid patterns showed intra‐ and intercalibration repeatability of 93% and 91%, respectively. Extremely low midleaf (0.15 ± 0.05%) and interleaf (0.27 ± 0.22%) transmission was measured, with no significant rotational variation. The average penumbra was ~0.8 mm for all leaves at field center, with a range of 0.17 mm for all leaf positions. A highly concave test plan was delivered with a ~ 95% gamma analysis pass rate, and a realistic mouse phantom liver irradiation plan achieved a pass rate of ~98%. A highly complex dose distribution was also created with 551 SOC apertures averaging 2.4 mm in size. Conclusions: A sparse orthogonal collimator was developed and commissioned, with promising preliminary dosimetry results. The SOC design, with its limited moving components and high dose‐modulation resolution, is ideal for delivering high‐quality small animal IMRT with our RAO‐based treatment planning system. Abstract :